Early tension regulation coupled to surface myomerger is necessary for the primary fusion of C2C12 myoblasts - Chakraborty, Madhura; Sivan, Athul; Biswas, Arikta; Sinha, Bidisha (Frontiers in Physiology, 2022)
Here we study the time-dependent regulation of fluctuation-tension during myogenesis and the role of the fusogen, myomerger. We measure nanometric height-fluctuations of the basal membrane of C2C12 cells after triggering differentiation. Fusion of cells increases fluctuation-tension but prefers (at 2-24 hr) a transient lowering of tension. Cells fail to fuse if early tension is continuously enhanced by methyl-b-cyclodextrin (MbCD). Perturbing tension regulation also reduces fusion. During this pre-fusion window, cells that finally differentiate usually display lower tension than other non-fusing cells validating early tension states to be linked to fate decision. Early tension reduction is accompanied by low but gradually increasing level of surface myomerger. Locally, too, regions with higher myomerger intensity display lower tension. However, this negative correlation is lost in the early phase by MbCD-based cholesterol depletion or later as differentiation progresses. We find that with tension and surface-myomerger’s enrichment under these conditions, myomerger clusters become pronouncedly diffused. We, therefore, propose that low tension aided by clustered surface-myomerger at the early phase is crucial for fusion and can be disrupted by cholesterol-reducing molecules implying potential to affect muscle health.